"MAD GOAT PROJECT." - Ventuzelos, Luis Fernando Pereira (2024)
The ever-changing technological landscape demands a greater effort on security best practices. Security in software is a responsibility shared by all. It is the responsibility of the software developers who are building important platforms that keep the world running, and it’s also the responsibility of the end-user who is utilizing said platforms. Software is everywhere and the need to have strong, independent systems that secure it is a must. Modern Application Development (MAD) makes use of a series of building blocks, like microservices, containerized applications, infrastructure as code, open-source software, and API communication. In today’s landscape, a single application can have dozens of independent services communicating with one another, and the relation between all these services can be hard to grasp for the security testing tools available in the market. The MAD Goat project is a web-based software platform that takes into consideration all the MAD building blocks while offering a vulnerable application by nature. This vulnerable application will serve as a security benchmark project to understand the quality of different security test scanners. The application has also an educational focus in its nature, offering its users an interactive learning experience. Through engaging lessons, users can enhance their understanding of the main vulnerabilities associated with MAD and develop mitigation strategies.